Gaze behaviour in offside decision-making in football: A field study - Schnyder, U.; Koedijker, M.; Kredel, R.; Hossner, E. J. (German Journal of Exercise and Sport Research, 2017)
The current study aims to determine the relationship between gaze characteristics and decision-making of expert and near-expert assistant referees in judging offside in football. Six assistant referees with different levels of expertise judged set-played offside scenes on the football field, while their gaze behaviour was measured with a mobile eye tracker. The location of gaze, numbers of fixations and temporal characteristics of the final fixation around the decisive pass were analysed to compare the two expertise levels and response accuracies. Expert assistant referees judged more offside situations correctly than near-experts, however, without any differences in gaze patterns. Irrespective of expertise, decision accuracy was higher for trials in which the assistant referees focussed on the offside line rather than on receiving attackers or one of the other defenders at the moment of the pass. Moreover, strong trends were observed for the positive effects of an overall "quiet" gaze behaviour and, in particular, of long final fixations on correct decisions. Thus, maintaining a stable gaze on the offside line around the moment of the decisive pass should be regarded as a superior strategy for assistant referees to optimise decision-making.